2017
DOI: 10.1186/s12879-017-2225-z
|View full text |Cite
|
Sign up to set email alerts
|

Viral aetiology of bronchiolitis in hospitalised children in Qatar

Abstract: BackgroundBronchiolitis is considered one of the earliest and most common causes of hospitalisation in young children. Development of molecular technologies allowed a better understanding of bronchiolitis aetiology. Results from cohort studies evaluating the association between single, multiple viral infections and clinical outcomes are conflicting. Data on viral bronchiolitis in children were found to be limited in Qatar. This study aimed to determine frequency and seasonal trends of viral pathogens causing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 31 publications
7
23
1
Order By: Relevance
“…A large, multicenter, multiyear prospective study of children hospitalized with bronchiolitis in 16 hospitals in the USA found that in comparison with children with RSV-only infections, those infected with RSV in combination with human rhinovirus (HRV) were more likely to have an LOS of 3 days or more and that those with HRV-only infections were less likely to present this outcome 39. An observational study that included 369 patients admitted to the pediatric ward for bronchiolitis detected RSV in 51.2% of the cases and in second place HRV in 25.5% of cases, but found that identifying the viral agent did not influence disease severity or LOS 28. In our study RSV isolation was associated with almost two times higher odds of prolonged LOS for bronchiolitis.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…A large, multicenter, multiyear prospective study of children hospitalized with bronchiolitis in 16 hospitals in the USA found that in comparison with children with RSV-only infections, those infected with RSV in combination with human rhinovirus (HRV) were more likely to have an LOS of 3 days or more and that those with HRV-only infections were less likely to present this outcome 39. An observational study that included 369 patients admitted to the pediatric ward for bronchiolitis detected RSV in 51.2% of the cases and in second place HRV in 25.5% of cases, but found that identifying the viral agent did not influence disease severity or LOS 28. In our study RSV isolation was associated with almost two times higher odds of prolonged LOS for bronchiolitis.…”
Section: Discussioncontrasting
confidence: 53%
“…The presence of cyanosis was significantly associated with prolonged LOS in a population of 1046 children hospitalized for acute lower respiratory infections in a hospital located in Cairo, Egypt 32. Janahi et al 28 in a retrospective cohort study examined an inpatient population of 369 infants admitted with acute bronchiolitis in a hospital in Qatar, and found that retraction was an independent predictor of longer LOS. Finally, Mansbach et al 33 identified decreasing lowest oxygen saturation in the ED as a variable independently associated with ED LOS.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at the primary outcome of duration of respiratory support via any mode, there was no difference between the two groups with a median duration of respiratory [1][2][3][4] in the more than one virus group (p ¼ 0.06). The median duration of hospital LOS was 4 days (IQR: 3-6) in the one virus group and 5 days (IQR: [4][5][6][7][8][9] in the more than one virus group (p ¼ 0.03).…”
Section: Resultsmentioning
confidence: 97%
“…3 Respiratory syncytial virus (RSV), followed by rhinovirus, seem to be the most prevalent pathogens. [3][4][5] Influenza, parainfluenza, metapneumovirus, adenovirus, and coronavirus are also frequently identified and might be responsible for greater illness severity. 3 The treatment for bronchiolitis, irrespective of the pathogen, is supportive and includes different levels of respiratory assistance that range from oxygen delivered via lowflow nasal cannula to invasive mechanical ventilation (IMV).…”
Section: Introductionmentioning
confidence: 99%
“…Influence of seasonal activity of the most commonly detected respiratory viruses has been reported in the literature. 13,14 According to Heyman et al, respiratory syncytial virus is the dominant pathogen during the winter months whereas rhinovirus is more common during other months. 15 However, we did not identify the virus.…”
Section: Discussionmentioning
confidence: 99%